Antecedents and Consequences of Visitor Attitude Toward Raja Ali Haji Batam Museum - Sulawati, Amel; Ernawadi, Yadi (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
Despite the growing need for museums to attract and retain visitors, there's a gap in understanding what truly drives visitor recommendations. This research aimed to investigate the influence of educational, esthetic, tour guide performance, and authenticity on recommendation intention, mediated by visitor attitude, within the context of the Raja Ali Haji Museum in Batam. This study uses cognitive appraisal theory as the underpinning theory. Data were collected from 120 visitors using a cross-sectional research design. Data analysis was conducted using Smart-PLS 3.0, encompassing assessments of outer model measurements, including convergent validity, discriminant validity, and composite reliability. The hypothesis test results indicate that educational, tour guide performance, and authenticity indirectly influence recommendation intention through visitor attitude, while esthetic appeal directly influences recommendation intention. These findings highlight the critical role of visitor attitude as a mediator for several key museum attributes, underscoring the nuanced pathways to fostering visitor recommendations. This research contributes to marketing science by introducing authenticity as an exogenous variable to the existing conceptual model and by adding novel hypotheses regarding visitor attitude influenced by tour guide performance, and recommendation intention influenced by educational, esthetic, tour guide performance, and authenticity.